Determination of flame retardants and Poly- and Perfluoroalkyl substances in indoor dust in Greater Cairo: assessment of human exposure. - Hassan, Yasmeen (AUC Knowledge Fountain, 2015)
This thesis dissertation examines the presence and exposure of two classes of compounds; polybrominated diphenyl ethers (PBDEs) and polyfluorinated compounds (PFCs). Both classes are considered persistent organic pollutants as they are toxic, bio-accumulative and have a high susceptibility to be environmentally dispersed. The PBDEs are typically used as protective agents on household appliances and furniture to retard the startup of fires; PFCs on the other hand are used as oil and water repellants. Few studies have investigated the presence of polybrominated diphnely ethers (PBDEs), novel flame retardants (FRs / non-PBDEs) and poly- and perfluoroalkyl compounds in Africa and the Middle East. These compounds have become ubiquitous, not only found in humans but also in animals and wildlife. Researches have shown that these toxic compounds can cause cancer, affect neurodevelopment, growth and other possible health risk. The main aim of this thesis was to investigate the levels of these contaminants and assess their associated human health risk. The levels of fourteen PBDE congeners and eleven non-PBDE flame retardants were investigated in 17 homes, 9 workplaces and 5 cars in the greater Cairo region. GC-MS was used for both the separation and quantification of the target analytes. Several parameters were calculated including the mean, median, minimum, maximum and four different percentiles. The median ΣPBDE concentrations were 57, 425 and 1608 ng g−1 in homes, workplaces and cars respectively. It was observed that congener 209 was dominant in all samples in the three different microenvironments with a median concentration of 40.2, 366 and 1540 ng g−1 in homes, workplaces and cars respectively representing 70 to 95% of the total PBDEs. Several novel PBDEs were investigated including hexabromocyclododecane (HBCD), hexabromobenzene (HBB), 2-ethylhexyl-2,3,4,5-tetrabromobenzoate (EH-TBB), bis (2-ethyl-1-hexyl) tetrabromophthalate (TBPH), 1,2-bis (2,4,6-tribromophenoxy) ethane (TBPE), ally-2,4,6-tribromophenyl ether (ATE) and Dechlorane Plus (DP). The Σnon-PBDEs median concentrations were 8.30, 28.9 and 49.9 ng g−1 in homes, workplaces and cars respectively with HBCD predominating. Four groups of analytes were investigated in the PFCs including: fluorotelomer acrylates (FTA), fluorotelomer alcohols (FTOH), Methyl/Ethyl perfluorooctane sulfonamides (Me/Et FOSA), Methyl/Ethyl perfluorooctane sulfonamidoethanols (Me/Et FOSE). Concentration of the PFASs ranged from 1.3 to 69 ng g−1 with FTOHs being the dominant. The highest FTOH was 8:2 FTOH detected in all samples in the three microenvironments. Results show that levels of PBDEs, non-PBDEs and PFCs in the Egyptian dust were among the lowest worldwide. Different dust exposure scenarios using 5th percentile, median, 95th percentile and maximum levels were estimated for adult and children. The estimated dust intake results were several orders of magnitude lower than the oral reference dose values.